Economic Growth and Urban Poverty in India. (March 2018) - Dubey, Amaresh; Tiwari, Shivakar
Urban poverty in most of the developing world is considered a spillover of rural poverty. With increasing pace of development in these countries, urban settlements are assimilating migrants searching for better livelihood opportunities and who could be vulnerable and poor in the urban settlements. This article empirically assesses the levels of urban poverty in India at the disaggregated level and examines how recent growth episode has impacted poverty reduction. This article finds that growth in general has been reducing poverty, but its effect in reducing poverty over different geographical domain has not been uniform. We find that rising inequality is playing a significant role in differential reduction of urban poverty in India and in its states.